Improving Competency Through Employee Performance - Timbul H Manullang, Hendrik; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
Human Resources (HR) are very important and must be possessed in an effort to achieve organizational or company goals. Human resources are the main element of an organization compared to other resource elements such as capital and technology, because humans themselves control other factors. The problem that occurs as a phenomenon in the BPJS Employment organization Tanjung Morawa and Pematang Siantar Branches is that the quality of human resources is still not good, meaning that organizational goals have not been achieved, the lack of training and knowledge makes employees less qualified in responding to their work so that employee performance is inadequate and they have to do a lot of training. , not all employees also have good competence in their abilities so that there is still a lot of work not completed on time. The results of this research are as follows:Competency has a positive and significant effect on employee performance with an original sample value of 0.498 and a p value of 0.000 <0.05. HR quality has a positive and significant effect on employee performance with an original sample value of 0.445 and a p value of 0.000 <0.05. Human resource quality has a positive and significant effect on competency with an original sample value of 0.814 and a p value of 0.000 <0.05. HR quality has a positive and significant indirect effect on employee performance through competency with an original sample value of 0.405 and a p value of 0.000.